2004
DOI: 10.2139/ssrn.913460
|View full text |Cite
|
Sign up to set email alerts
|

General Quadratic Term Structures for Bond, Futures, and Forward Prices

Abstract: For finite dimensional factor models, the paper studies general quadratic term structures. These term structures include as special cases the affine term structures and the Gaussian quadratic term structures, previously studied in the literature. We show, however, that there are other, non-Gaussian, quadratic term structures and derive sufficient conditions for the existence of these general quadratic term structures for bond, futures and forward prices.As forward prices are martingales under the T -forward me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…in El Karoui et al [12], Pelsser [29], Gombani and Runggaldier [17], Leippold and Wu [24], Chen et al [5], and Gaspar [16]. However, since the pre-crisis exponentially affine models are more common, there have also been more attempts to extend them to a post-crisis multi-curve setting (for an overview and details see e.g.…”
Section: The Modelmentioning
confidence: 99%
“…in El Karoui et al [12], Pelsser [29], Gombani and Runggaldier [17], Leippold and Wu [24], Chen et al [5], and Gaspar [16]. However, since the pre-crisis exponentially affine models are more common, there have also been more attempts to extend them to a post-crisis multi-curve setting (for an overview and details see e.g.…”
Section: The Modelmentioning
confidence: 99%
“…In [14] and [8] it is was shown that the so-called linearquadratic jump-diffusion (LQJD) models are equivalent to the AJD models with an augmented state vector.…”
Section: Extension Of Stochastic Volatility Equity Modelsmentioning
confidence: 99%
“…For the risk-free bond market we use the general quadratic term structures setup studied in Gaspar (2004). Consider a finite set of time-dependent factors described by a R m -valued stochastic process (Z t ) t≥0 .…”
Section: Risk-free Bond Marketmentioning
confidence: 99%
“…Moreover, Q(t) is assumed to be symmetric 2 for all t. Gaspar (2004) has shown how to identify these factors a priori from their impact on the drift α, volatility σ or the functional form of the short rate. We, thus, classify the components of Z in the following two groups.…”
Section: W T T≥0mentioning
confidence: 99%
See 1 more Smart Citation